Differentiated swine airway epithelial cell cultures for the investigation of influenza A virus infection and replication. Issue 2 (25th April 2012) - Bateman, Allen C.; Karasin, Alexander I.; Olsen, Christopher W.
Abstract : Please cite this paper as: Bateman et al. (2013) Differentiated swine airway epithelial cell cultures for the investigation of influenza A virus infection and replication. Influenza and Other Respiratory Viruses 7(2) 139–150. Background  Differentiated human airway epithelial cell cultures have been utilized to investigate cystic fibrosis, wound healing, and characteristics of viral infections. These cultures, grown at an air–liquid interface (ALI) in media with defined hormones and growth factors, recapitulate many aspects of the in vivo respiratory tract and allow for experimental studies at the cellular level. Objectives  To optimize growth conditions for differentiated swine airway epithelial cultures and to use these cultures to examine influenza virus infection and replication. Methods  Primary swine respiratory epithelial cells were grown at an air–liquid interface with varying amounts of retinoic acid and epidermal growth factor. Cells grown with optimized concentrations of these factors for 4 weeks differentiated into multilayer epithelial cell cultures resembling the lining of the swine respiratory tract. Influenza virus infection and replication were examined in these cultures. Results/Conclusions  Retinoic acid promoted ciliogenesis, whereas epidermal growth factor controlled the thickness of the pseudoepithelium. The optimal concentrations for differentiated swine cell cultures were 1·5 ng/ml epidermal growth factor and 100 nm retinoic acid. Influenza A viruses infected and productively replicated in these cultures in the absence of exogenous trypsin, suggesting that the cultures express a protease capable of activating influenza virus hemagglutinin. Differences in virus infection and replication characteristics found previously in pigs in vivo were recapitulated in the swine cultures. This system could be a useful tool for a range of applications, including investigating influenza virus species specificity, defining cell tropism of influenza viruses in the swine respiratory epithelium, and studying other swine respiratory diseases.